Potential Use of Microbial Enzymes for the Conversion of Plastic Waste Into Value-Added Products: A Viable Solution - Tamoor, Muhammad; Samak, Nadia A.; Jia, Yunpu; Mushtaq, Muhammad Umar; Sher, Hassan; Bibi, Maryam; Xing, Jianmin (Frontiers in Microbiology, 2021)
The widespread use of commercial polymers composed of a mixture of polylactic acid and polyethene terephthalate (PLA-PET) in bottles and other packaging materials has caused a massive environmental crisis. The valorization of these contaminants via cost effective technologies is urgently needed to achieve a circular economy. The enzymatic hydrolysis of PLA-PET contaminants plays a vital role in environmentally friendly strategies for plastic waste recycling and degradation. In this review, the potential roles of microbial enzymes for solving this critical problem are highlighted. Various enzymes involved in PLA-PET recycling and bioconversion, such as PETase and MHETase produced by Ideonella sakaiensis; esterases produced by Bacillus and Nocardia; lipases produced by Thermomyces lanuginosus, Candida antarctica, Triticum aestivum, and Burkholderia spp.; and leaf-branch compost cutinases are critically discussed. Strategies for the utilization of PLA-PET’s carbon content as C1 building blocks were investigated for the production of new plastic monomers and different value-added products, such as cyclic acetals, 1,3-propanediol, and vanillin. The bioconversion of PET-PLA degradation monomers to polyhydroxyalkanoate biopolymers by Pseudomonas and Halomonas strains was addressed in detail. Different solutions to the production of biodegradable plastics from food waste, agricultural residues, and polyhydroxybutyrate-accumulating bacteria were discussed. Fuel oil production via PLA-PET thermal pyrolysis and possible hybrid integration techniques for the incorporation of thermostable plastic degradation enzymes for the conversion into fuel oil is explained in detail.